Private Paris [compact disc, unabridged] - Patterson, James, 1947-; Sullivan, Mark T. (Patterson, James, 1947- Private novels., 2016)
When Jack Morgan stops by Private's Paris office, he envisions a quick hello during an otherwise relaxing trip filled with fine food and sightseeing. But Jack is quickly pressed into duty after a call from his client Sherman Wilkerson, asking Jack to track down his young granddaughter who is on the run from a brutal drug dealer.